European Union training programme for tuberculosis laboratory experts: design, contribution and future direction - Philomena Raftery; Csaba Ködmön; Marieke J. van der Werf; Vladyslav Nikolayevskyy (BMC, 2020)
Abstract Background Tuberculosis (TB) control programmes rely heavily on laboratories to support both clinical care and public health. Qualified personnel with adequate technical and managerial skills comprise an integral component of any quality assured laboratory. Training a new generation of TB laboratory specialists was identified as a critical priority in the European Union /European Economic Area (EU/EEA). A tailored training programme for TB reference laboratory professionals was developed and implemented within the European Reference Laboratory Network for Tuberculosis to increase the pool of technical experts available to step into leadership roles in the TB laboratory community. Three cohorts of selected laboratory specialists participated in a series of trainings from 2009 to 2016. Methods We conducted an evaluation of the training programme using a structured questionnaire administered via the EUSurvey website, with the aim of documenting the benefits and contribution as well as suggesting improvements and future direction of the programme. All graduated participants and all current ERLTB-Net members were invited to participate in the online survey and descriptive quantitative analysis was performed. Results The evaluation found significant benefits for both the participants and the participants' institutions, with improvements being reported in laboratory practices and management including implementation of new diagnostic techniques and career progression for participants. The training programme differed from other international and European initiatives in a number of important ways; the curriculum is unique in the scope and range of topics covered; the programme targets senior level professionals and future directors; cohorts were limited to 8-10 participants; and the programme involved a number of workshops (5-7) taking place over a two-year period. Relationships and collaborations established between individuals and institutions were valued as an important success of the initiative. Suggestions on how the impact of the programme could be enhanced included equipping participants to perform laboratory assessments in low-resource settings outside the EU, thus bolstering global TB control. Conclusion Based on the findings presented the training programme has proved to be successful in developing leadership, expertise, partnerships and networks to support TB laboratories and has contributed significant benefits to strengthening European National Reference laboratories in the fight against TB.